Selecting best routes of Iraqi cities using Genetic Algorithem (مجلة المنصور, 2023)
The Genetic Algorithms can be considered as modern active way for finding optimum solution for many engineering problems as where as electronics , power , communication engineering. This optimum location has been detected with a low number of iteration . this optimazation can be used for many civilian application such as location of electrical power station , location of communication center or other to reduce the price/ km for transmission line . this optimization problem have been run with a special genetic algorithm called ( Gas play ground ) with suitable genetic input file.